- Writing and Solving One-Step Equations
- Home
- Solving a One-Step Linear Equation Problem Type 1
- Solving a One-Step Linear Equation Problem Type 2
- Additive Property of Equality With Whole Numbers
- Solving an Equation With Multiplication or Division
- Multiplicative Property of Equality With Whole Numbers
- Translating a Sentence Into a One-Step Equation

- Selected Reading
- UPSC IAS Exams Notes
- Developer's Best Practices
- Questions and Answers
- Effective Resume Writing
- HR Interview Questions
- Computer Glossary
- Who is Who

# Solving a One-Step Linear Equation Problem Type 2 Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to **Solving a One-Step Linear Equation Problem Type 2**. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using **Show Answer** button. You can use **Next Quiz** button to check new set of questions in the quiz.

### Answer : A

### Explanation

**Step 1:**

16 – 4y = 12

Subtracting 16 from both sides

**Step 2:**

16 – 4y – 16 = 12 – 16 = − 4

− 4y = − 4

**Step 3:**

Dividing both sides by – 4

So, y = 1

### Answer : C

### Explanation

**Step 1:**

4w + 6 = 18

Subtracting 6 from both sides

**Step 2:**

4w + 6 – 6 = 18 – 6 = 12

4w = 12

**Step 3:**

Dividing both sides by 4;

$\frac{4w}{4}$ = $\frac{12}{4}$ = 3

So, w = 3

### Answer : B

### Explanation

**Step 1:**

1 + 6p = 13

Subtracting 1 from both sides

**Step 2:**

1 + 6p – 1 = 13 – 1 = 12

6p = 12

**Step 3:**

Dividing both sides by 6 we get

$\frac{6p}{6}$ = $\frac{12}{6}$ = 2

So, p = 2

### Answer : D

### Explanation

**Step 1:**

7 + 2z = 19

Subtracting 7 from both sides

**Step 2:**

7 + 2z – 7 = 19 – 7 = 12

2z = 12

**Step 3:**

Dividing both sides by 2;

$\frac{2z}{2}$ = $\frac{12}{2}$ = 6

So, z = 6

### Answer : C

### Explanation

**Step 1:**

20 – 5m = 5

Subtracting 20 from both sides

**Step 2:**

20 – 5m – 20 = 5 – 20 = − 15

− 5m = − 15;

**Step 3:**

Dividing both sides by −5,

$\frac{-5m}{-5}$ = $\frac{-15}{-5}$ = 3

So, m = 3

### Answer : B

### Explanation

**Step 1:**

3t + 1 = 16

Subtracting 1 from both sides

**Step 2:**

3t + 1 – 1 = 16 – 1 = 15

3t = 15;

**Step 3:**

Dividing both sides by 3

$\frac{3t}{3}$ = $\frac{15}{3}$ = 5

So, t = 5

### Answer : A

### Explanation

**Step 1:**

7 = 3k − 5

Adding 5 to both sides

**Step 2:**

7 + 5 = 3k – 5 + 5 = 3k

3k = 12

**Step 3:**

Dividing both sides with 3

$\frac{3k}{3}$ = $\frac{12}{3}$ = 4

So, k = 4

### Answer : D

### Explanation

**Step 1:**

3x + 4 = 13

Subtracting 4 from both sides

**Step 2:**

3x + 4 – 4 = 13 – 4 = 9

3x = 9;

**Step 3:**

Dividing both sides with 3

$\frac{3x}{3}$ = $\frac{9}{3}$ = 3

So, x = 3

### Answer : C

### Explanation

**Step 1:**

6 = 2q − 4

Adding 4 to both sides

**Step 2:**

6 + 4 = 2q – 4 + 4 = 2q

2q = 10

**Step 3:**

Dividing both sides by 2

$\frac{2q}{2}$ = $\frac{10}{2}$ = 5

So, q = 5

### Answer : B

### Explanation

**Step 1:**

8 + 2x = 12

Subtracting 8 from both sides

**Step 2:**

8 + 2x – 8 = 12 – 8 = 4

2x = 4;

**Step 3:**

Dividing both sides by 2

$\frac{2x}{2}$ = $\frac{4}{2}$ = 2

So, x = 2